Satisfaction of readers towards the characteristics of 'Perempuan' magazine / Azi Zulfira Abdul Rahim (Faculty of Business and Management, 2008)
The level of satisfaction is very important in any business settings, whether product or service businesses, In the publishing industry, keeping a customer satisfied is the utmost importance in order to maintain the number of readers and also to maintain profit. In this research, a study is made to identify the level of satisfaction towards the characteristics of a magazine, in particular the 'Perempuan' magazine. For the purpose of this study, an exploratory research was employed. Also this research involves descriptive research, in order to identify the satisfaction level of readers of 'Perempuan' magazine. Non probability sampling has been used with a sample size of 31 respondents. As the survey instrument, questionnaires were distributed to the readers of the magazine. The data collected was generated using the SPSS (Statistical Package for the Social Science), and then the results are analyzed. The results attained were in form of frequency tables and reliability testing. The findings of this study conclude that the readers of 'Perempuan' magazine have only a moderate level of satisfaction towards the price and the layout and design of the magazine. Readers of 'Perempuan' however are satisfied with the contents of the magazine. The overall level of satisfaction towards the magazine is in a moderate level.